Torta de girassol e suplementação multienzimática em rações para frangas: digestibilidade, balanço de minerais e parâmetros de crescimento e qualidade óssea - Souza, Otoniel Félix de (2019)
Four objective experiments on the digestibility and mineral balance, growth parameters and bone quality of light and medium pullets were studied. For each seed, two experiments were conducted, and initially only one inclusion of sunflower cake. Already in the second experiment carried out for each lineage where the association of two levels of sunflower cake and enzymatic complex were tested. Thus, in experiment I, 756 light line pullets were used, distributed in a completely randomized design with six treatments and six replicates of 21 birds each, which were submitted to rations with the inclusion of 0, 5, 10, 15, 20 and 25 % of sunflower cake. In the experiment II, 450 litters of light lineage were used in the plots following a completely randomized experimental design in a factorial scheme 2x2 + 1, totaling five treatments with six replicates of 18 birds, being tested two levels of sunflower cake, 10 and 20% and two forms of multienzymatic supplementation (absence and presence) and a control diet based on corn and soybean meal. In the experiments with semipesed pullets, III and IV, the same number of birds and experimental designs used in experiment I and II, respectively, differing only for the inclusion level of the sunflower cake were 0, 6, 12, 18, 24 and 30% for experiment III, and levels 12 and 24% in experiment IV. To assess the bone quality, one bird per plot was slaughtered at week 17 of age and the bones of the tibia were used to measure length, weight, Seedor index, resistance, deformity. Bone samples were analyzed for dry matter, ashes and minerals for determination of composition. The data of the experiments I and III were submitted to analysis of variance, comparison of means by the Dunnett test and regression. The data of the experiments II and IV were submitted to analysis of variance, according to the factorial scheme adopted in the outline, and the means were compared by the SNK test. In the experiments in which only inclusion levels of sunflower cake were tested in the poultry ration, it was verified that the inclusion of up to 25% of the sunflower cake for light and 30% for semipesic pullets did not influence the digestibility of calcium, phosphorus, magnesium and its balance, as well as did not affect the composition and parameters of bone quality. In the experiments with light and medium-weight pullets in which the two levels of sunflower cake associated with multienzyme supplementation were evaluated, it was observed in both cases that there was no interaction between levels of sunflower cake and enzymatic supplementation, as well as effect of the level of the sunflower cake for the digestibility and balance of calcium, phosphorus and magnesium, composition and parameters of bone quality. However, in both experiments, the presence of the multienzyme complex provided a significant improvement in the digestibility coefficient of the Ca, P and Mg of the diets. It can be concluded that the sunflower cake can be used in the growth rations up to the levels of 25% for light pullets and 30% for pullets semipesadas; and that multienzymatic supplementation in diets containing sunflower cake improves the digestibility of dietary minerals. In all experiments in the period between the 14th and 15th week, metabolism tests were carried out, using the total excreta collection method to determine the digestibility coefficient of the dietary minerals.